Dietary supplementation of organic selenium to improve growth performance and protein utilization in African catfish fed with different protein level diets - Darmawangsa, Giri Maruto; Suprayudi, Muhammad Agus; Utomo, Nurbambang Priyo; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2021)
This study aimed to evaluate the effect of organic selenium supplementation on diet with different protein levels on the growth performance and protein utilization of African catfish juvenile. A randomized 2×3 factorial design with two dietary protein levels (27% and 32%) and three dietary selenium (Se) supplementation levels (0 mg/kg, 3 mg/kg, and 6 mg/kg diet) in triplicates were applied in the study. African catfish juvenile with an initial average body weight and body length of 27.00 ± 0.14 g and 15.0 ± 0.5 cm, respectively, was reared in 18 units of aquarium (141 L) at a density of 142 fish/m3 for a rearing period of 40 days. Increasing organic Se supplementation level up to 6 mg/kg at high protein feed resulted in higher fish growth and final biomass, lower FCR, and higher protein utilization efficiency than those of other treatments. Furthermore, supplementation of organic Se also resulted in lower lipid and higher Se concentrations in the fish body as well as higher blood protein level compared to those of the control. In conclusion, the result of this study suggested that dietary supplementation of organic Se up to 6 mg/kg could enhance the growth and protein utilization in African catfish fed with both low and high protein diet. Keywords: African catfish, growth, dietary protein, protein utilization, organic selenium. ABSTRAK Penelitian ini bertujuan mengevaluasi pengaruh suplementasi selenium organik pada pakan dengan kadar protein yang berbeda terhadap kinerja pertumbuhan dan pemanfaatan protein pakan ikan lele Clarias gariepenus. Penelitian didesain menggunakan rancangan acak lengkap faktorial 2×3 dengan dua tingkat protein pakan (27% dan 32%) dan tiga tingkat suplementasi selenium (Se) pakan (0 mg/kg, 3 mg/kg, dan 6 mg/kg diet) sebanyak tiga ulangan. Ikan lele yang digunakan memiliki bobot awal rata-rata dan panjang tubuh 27 ± 0.14 g dan 15.0 ± 0.5 cm, dipelihara dalam 18 unit akuarium (141 L) dengan kepadatan 142 ekor/m3 selama 40 hari pemeliharaan. Peningkatan suplementasi Se organik hingga 6 mg/kg pada ikan yang diberi pakan protein tinggi menghasilkan kinerja pertumbuhan ikan dan biomassa akhir yang lebih tinggi, FCR yang lebih rendah, dan efisiensi pemanfaatan protein pakan yang lebih tinggi daripada perlakuan lain. Selain itu, suplementasi Se organik juga menghasilkan kadar lemak yang lebih rendah dan konsentrasi Se tubuh yang lebih tinggi serta kadar protein darah yang lebih tinggi. Kesimpulan dari penelitian ini yaitu suplementasi Se organik pada pakan hingga 6 mg/kg dapat meningkatkan kinerja pertumbuhan dan pemanfaatan protein pakan pada ikan lele yang diberi pakan dengan kadar protein rendah dan tinggi. Kata kunci: ikan lele, pertumbuhan, protein pakan, pemanfaatan protein, selenium organik.